2019
DOI: 10.1016/j.ast.2018.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Ablative thermal protection system under uncertainties including pyrolysis gas composition

Abstract: Spacecrafts such as Stardust (NASA, 2006) are protected by an ablative Thermal Protection System (TPS) for their hypersonic atmospheric entry. A new generation of TPS material, called Phenolic Impregnated Carbon Ablator (PICA), has been introduced with the Stardust mission. This new generation of low density carbon-phenolic composites is now widely used in the aerospace industry. Complex heat and mass transfer phenomena coupled to phenolic pyrolysis and pyrolysis gas chemistry occur in the material during atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…However, it lacks in generality and fails when applied to largely different heating rates. For ablation modeling at varying heating rates this is a substantial limitation, no longer acceptable as we aim at physics-based predictions of the ablation phenomenon [14]. Indeed, a broad range of heating rates is found in ablative heat shields used in atmospheric entry.…”
mentioning
confidence: 99%
“…However, it lacks in generality and fails when applied to largely different heating rates. For ablation modeling at varying heating rates this is a substantial limitation, no longer acceptable as we aim at physics-based predictions of the ablation phenomenon [14]. Indeed, a broad range of heating rates is found in ablative heat shields used in atmospheric entry.…”
mentioning
confidence: 99%
“…The Phenolic Impregnated Carbon Ablator (PICA) developed at NASA Ames Research Center is a state-of-the-art carbon/phenolic ablator, which exhibits low mass per unit volume and superior ablation property. Research results have confirmed that PICA offers outstanding anti-ablation performance, along with a low-density property (about 0.2-0.4 g/cm 3 ) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 77%
“…The serious heating flow formed by the intense friction between a hypersonic vehicle and the surrounding air severely affects the flight stability of an aircraft [1][2][3][4]. Carbon fabric reinforced phenolic (C-Ph) composites possessing high thermal stability and good mechanical property is an ideal ablative heat-preventing material, which was widely used for thermal protection systems [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%